On a Class of q-bi-univalent Functions of Complex Order Related to Shell-Like Curves Connected With the Fibonacci Numbers - Ahuja, Om P.; ÇETİNKAYA, ASENA; Bohra, Nisha (Honam Mathematıcal Soc., 2020)
We introduce a new subclass of q-bi-univalent functions of complex order related to shell-like curves connected with the Fibonacci numbers. We obtain the coefficient estimates and Fekete-Szego inequalities for the functions belonging to this class. Relevant connections with various other known classes have been illustrated.
Keywords: Fekete-Szego